The Relationship Between Technology Acceptance Factors and Ride E-Hailing Service Adoption - Rashid, Nurul Safika; Azizan, Anim Zalina (Research in Management of Technology and Business, 2026)
The rapid growth of app-based e-hailing services has reshaped mobility patterns in urban areas by offering flexible, on-demand travel options, yet persistent issues related to user safety, digital capability, and data privacy remain particularly relevant in developing towns such as Batu Pahat. This study investigates the extent of technology acceptance among youths in Batu Pahat, examines their level of ride e-hailing usage, and analyses the association between acceptance factors and service adoption. A quantitative survey design was employed, involving 303 youth respondents, using a structured questionnaire measuring perceived ease of use, perceived usefulness, and user attitudes, with data analysed through descriptive statistics and Spearman’s rho correlation. The results show that youths in Batu Pahat demonstrate strong acceptance of e-hailing applications and favourable attitudes toward their use, with statistically significant and positive relationships identified among ease of use, usefulness, and attitude variables (p<0.01). Overall, the findings indicate that usability and functional value are central in shaping youth acceptance of e-hailing services in semi-urban contexts, and they offer practical direction for service providers to enhance digital inclusion, user confidence, and the effectiveness of app-based transport systems, while encouraging future research explore the model’s expansion through the integration of additional variables, including trust, perceived risk, social influence, and cost considerations.